Is Transit-Oriented Development (TOD) Project Financially Feasible? A Case Study from Emerging Economies - Herawati Zetha Rahman; Imam Hagni Puspito; I Nyoman Teguh; Najwa; Caroline Krisnadewi (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2026)
Transit-Oriented Development is a crucial strategy for addressing urban sprawl and improving mobility, particularly in rapidly urbanizing regions like Indonesia. Transit-Oriented Development integrates high-density, mixed-use developments with public transportation infrastructure, offering sustainable urban growth solutions. However, despite its benefits, the financial feasibility of Transit-Oriented Development in emerging economies remains under-explored. This study assesses the financial viability of a Transit-Oriented Development project in Tangerang, Greater Jakarta, focusing on key financial indicators such as Capital Expenditure, Operational Expenditure, Internal Rate of Return, and Net Present Value. The study uses financial modeling, analyzing data from the project's feasibility reports and investment summaries. The results show positive Internal Rate of Return, and Net Present Value, indicating financial viability under base case assumptions. However, the analysis reveals sensitivity to changes in Capital Expenditure and revenue assumptions, with increased Capital Expenditure reducing profitability and extending the payback period. This research fills the gap in Transit-Oriented Development financial feasibility studies in developing economies, providing valuable insights for similar projects in Southeast Asia and beyond. The findings underscore the importance of effective financial planning and risk management in ensuring the long-term success and sustainability of Transit-Oriented Development projects, highlighting the need for strong public-private partnerships to mitigate financial risks.